2020
DOI: 10.1101/2020.04.08.031344
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Runs of homozygosity in killer whale genomes provide a global record of demographic histories

Abstract: Runs of homozygosity (ROH) occur when offspring receive the same ancestral haplotype from both parents, and, accordingly, reduce individual heterozygosity. Their distribution throughout the genome contains information on the probability of inbreeding mediated by mating system and population demography. Here, we investigate variation in killer whale demographic history as reflected in genome-wide heterozygosity, using a global dataset of 26 genomes. We find an overall pattern of lower heterozygosity in genomes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Only individuals with an average genome‐wide coverage of 5× and above were included in the analysis of runs of homozygosity (ROHs) (136/141) as in Hooper et al . (2020). The largest 30 scaffolds for each of these individuals were selected for ROH analysis defined by a minimum length of 10 Mb.…”
Section: Methodsmentioning
confidence: 99%
“…Only individuals with an average genome‐wide coverage of 5× and above were included in the analysis of runs of homozygosity (ROHs) (136/141) as in Hooper et al . (2020). The largest 30 scaffolds for each of these individuals were selected for ROH analysis defined by a minimum length of 10 Mb.…”
Section: Methodsmentioning
confidence: 99%
“…However, a key insight from ROH studies has been that a large proportion of deleterious homozygous genotypes seem to fall into ROH (Szpiech et al, 2013), leading to the prediction that ROH detection could be one of the most powerful methods to investigate inbreeding depression (Keller et al, 2011). As genomic technologies have become more affordable, the opportunity to infer individual ROH in animals of high ecological importance or of conservation concern has therefore received increasing attention (Escoda & Castresana, 2021; Grossen et al, 2018; Humble et al, 2020; Hooer et al, 2020; Wang et al, 2021). For example, a large‐scale collared flycatcher ( Ficedula albicollis ) study on genomic inbreeding and historical demography found ROH sizes between 953 bp and 17.5 Mbp (Kardos et al, 2017), with highest ROH abundance in regions of low recombination rate.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, genetic diversity is also threatened under climate change. The decline in population size allows for inbreeding depression by reducing the genetic diversity and increasing recessive homozygotes created by consanguineous mating [78][79][80]. That would lead to a weakened resilience of populations against climate change effects and other anthropogenic pressures [81].…”
Section: Consequences On Reproductive Successmentioning
confidence: 99%